Impact of treatment policies on patient outcomes and resource utilization in acute cholecystitis in Japanese hospitals - Murakami Genki; Ishizaki Tatsuro; Hirose Masahiro; Imanaka Yuichi; Sekimoto Miho; Fukata Yushi (BMC, 2006)
Abstract Background Although currently available evidence predominantly recommends early laparoscopic cholecystectomy (LC) for the treatment of acute cholecystitis, this strategy has not been widely adopted in Japan. Herein, we describe a hospital-based study of patients with acute cholecystitis in 9 Japanese teaching hospitals in order to evaluate the impact of different institutional strategies in treating acute cholecystitis on overall patient outcomes and medical resource utilization. Methods From an administrative database and chart review, we identified 228 patients diagnosed with acute cholecystitis who underwent cholecystectomy between April 2001 and June 2003. In order to examine the relationship between hospitals' propensity to perform LC and patient outcomes and/or medical resource utilization, we divided the hospitals into three groups according to the observed to expected ratio of performing LC (LC propensity), and compared the postoperative complication rate, length of hospitalization (LOS), and medical charges. Results No hospital adopted the policy of early surgery, and the mean overall LOS among the subjects was 30.9 days. The use of laparoscopic surgery varied widely across the hospitals; the adjusted rates of LC to total cholecystectomies ranged from 9.5% to 77%. Although intra-operative complication rate was significantly higher among patients whom LC was initially attempted when compared to those whom OC was initially attempted (9.7% vs. 0%), there was no significant association between LC propensity and postoperative complication rates. Although the postoperative time to oral intake and postoperative LOS was significantly shorter in hospitals with high use of LC, the overall LOS did not differ among hospital groups with different LC propensities. Medical charges were not associated with LC propensity. Conclusion Under the prevailing policy of delayed surgery, in terms of the postoperative complication rate and medical resource utilization, our study did not show the superiority of LC in treating acute cholecystitis patients. The timing of surgery and discharge was mainly determined by the institutional policy in Japan, rather than by the clinical course of the patient; however, considering the substantially less postoperative pain and shorter recovery time of LC compared to OC, LC should be actively applied for the treatment of acute cholecystitis. If the policy of early surgery were universally applied, the advantage of LC over OC may be more clearly demonstrated.